Changing trends in the use of translation resources - Hirci, Nataša (ELOPE (Ljubljana), 2013)
This paper explore the changes detected in the utilization of translation resources by trainee translators working with the Slovene-English language pair in Slovenia. To test the assumption that rapid advances in information and communication technologies have made a significant impact on translation practice, a study involving two generations of translation students in Ljubljana was designed to examine whether their practice of using translation aids has changed over a certain period of time. This population will soon have to compete with their professional counterparts; it is therefore crucial they are fully equipped not only with the necessary translation knowledge, but also that they are skilled in advanced translation aids, as this will cater for the demands of the modern translation market where an efficient use of translation resources appears to be vital for successful intercultural communication. The results of the study indicate some changes can be detected even within a short period of time.
Keywords: bodoči prevajalci; izobraževanje prevajalcev; prevajalske tehnologije; prevajalski viri